Intergenerational service-learning through virtual exchange across a foreign language program - Carolin Fuchs (University of Groningen Press, 2024)
This paper reports on the implementation of intergenerational service-learning (SL) through virtual exchange (VE) across a German as a foreign language program at a private research institution on the East Coast in the U.S. The S-L integration started during the pandemic in intermediate courses as an outreach effort to Germanspeaking older adults in Germany and in the U.S. and has become a cornerstone of the German Program. Participants include intermediate and advanced German learners, two non-profit volunteer organizations in Germany that focus on improving the living conditions of older adults in society, one local U.S. community partner, and German heritage speakers in the U.S. Since Spring 2021, students have engaged with older adults in different formats (tandem, whole-group, a mix of both) via technology tools (landlines, Zoom, WhatsApp, Facetime). The Program is rooted in three experiential pedagogical approaches and frameworks, namely VE, S-L, and Intercultural Citizenship Education, which are driven by principles of reciprocity and reflection. The overall programmatic objective is to contribute to Diversity, Equity, Inclusion, and Belonging (DEIB) goals (community engagement, partnership formation) set forth in the institution's strategic plan. Course learning outcomes include fostering intergenerational, intercultural, and language learning and raising students' awareness towards challenges older adults may face. On the level of language program development, the Program provides opportunities for instructor-instructor collaborations, instructor-student collaborations, and communityengaged research.